Perancangan UI/UX Aplikasi Mobile Penjualan Pada Toko Up Store Menggunakan Figma - Ardi Mandani; 2Ahmad Mutatkin Bakti (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
In today's digital environment, mobile apps are essential to improve user experience and sales reach. The study will use Figma software design to create user interfaces (UI) and user experience (UX) for mobile app sales on the Up Store. Figma, an online prototyping platform, can be used to create web or mobile applications. Programmers can contribute to the figma project by writing their own code. The process used to create these designs is called Design Thinking. Design Thinking focuses on user understanding, idea development, and solution testing through an iterative cycle. This strategy will help in defining user needs, understanding the context of use, and creating acceptable and efficient designs. This research resulted in a mobile app UI/UX design that conforms to sound design principles and uses current sales trends in Up Store. If the user interface is designed well, users will interact with the app more positively, increasing user retention and sales. Figma also allows UI/UX designers and application developers to communicate more successfully during the design phase As well as based on the results of the EUCS dimensional engineering assessment, the results of the research that has been carried out are obtained Users are satisfied with the user interface design of the sciencom android application. This is shown based on a percentage of 92.5% of users strongly agree with the current user interface design.